The South African townscape: Conservation & development conflicts - van Zyl, Wallace (Acta Structilia, 1999)
This article examines some aspects of urban conservation practices in South Africa since World War Two. The conservation of individual homesteads in rural areas is being neglected in favour of the powerful inter-relationship and context implied by townscape. The continuation of this trend does not, however, mean that rural landscape conservation is unimportant, but rather indicates the primary need for sustainable townscaping.